The effect of application frequency of nitrogen fertilizer on the growth and yield of rice / Muhammad Khirul Iqbal Mat Asis - Mat Asis, Muhammad Khirul Iqbal (Faculty of Plantation and Agrotechnology, 2019)
Rice is an important crop in Malaysia other than rubber and oil palm. Nutrient management is a crucial thing in order to ensure the good growth performance and yield of rice. In order to study the effect of different application time of nitrogen fertilizer on the growth and yield of rice the experiment was carried out using Complete Randomized Design (CRD) on 4 treatments and 5 replications. (T0) was 4 times splits application nitrogen fertilizer which served as control, treatment 1 (T1) was 3 times splits application nitrogen fertilizer, treatment 2 (T2) 2 times splits application nitrogen fertilizer, and treatment 3 (T3) was 1 time of splits application nitrogen fertilizer. The variety of rice use is MR220 CL2. The parameter used in study are width of leaves, height of plant, number of tillers, number of panicle,1000-grain weight, fresh weight and dry weight. The results showed treatment 1 with 3 times of nitrogen fertilizer application showed positive result for the leaves width, height of plant, number of panicle, and 1000-grain weight. The treatment 2 and treatment 3 showed the lowest mean for all parameters and there is no significant difference between the treatment. From this study the 3 times application of nitrogen fertilizer was proved in boosting a better growth and yield of rice.